The Prognostic Value of Systemic Immune-Inflammation Index Supporting Age-Adjusted Charlson Comorbidity Index in Non-Small Cell Lung Cancer Patients with First-Line Platinum-Based Chemotherapy - Sheng YY; Zhu Q; Dai QB; Gao YJ; Bai YX; Liu MF (International Journal of General Medicine)
Yi-Yun Sheng,1 Qing Zhu,2 Qian-Bin Dai,2 Yu-Jie Gao,2 Yun-Xue Bai,2 Mei-Fang Liu2 1Department of Pathology, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of China; 2Department of Clinical Laboratory, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of ChinaCorrespondence: Mei-Fang Liu, Department of Clinical Laboratory, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of China, Tel +86 0791 86319430, Fax +86 0791 88692272, Email mfliu922@163.comPurpose: This study aimed to examine the association between the systemic immune-inflammation index (SII) (ie, neutrophil count × platelet count/lymphocyte count), the age-adjusted Charlson comorbidity index (ACCI), and overall survival (OS) in non-small cell lung cancer (NSCLC) patients undergoing first-line platinum-based chemotherapy (PBC), with a particular emphasis on the role of SII in supporting ACCI.Patients and Methods: This retrospective study enrolled 353 cases treated between July 2013 and November 2020. Mann–Whitney U-test and Kruskal–Wallis test were employed to compare parameters between high and low SII groups. The cut-off values for SII and ACCI were determined using the X-tile software. Prognostic significance was evaluated through the utilization of Kaplan-Meier curves and Cox regression analysis.Results: In a univariate Cox regression analysis, sex, age, TNM, lymph node, therapy, SII, and ACCI were associated with OS. After adjusting for confounders in the multivariate analysis, TNM, SII, and ACCI remained independent prognostic factors for OS. Furthermore, within the ACCI subgroups (ACCI< 5 or ACCI≥ 5), a high SII was significantly associated with an increased risk of death. Patients with both a high ACCI and a high SII had the highest risk of death (p < 0.001), with a loss of approximately ten months of survival during the first three years after treatment.Conclusion: SII was proven to be valuable in predicting OS and, when complemented by ACCI, can help tailor prognostic assessment and treatment strategies in assessing the survival of NSCLC patients with first-line PBC.Keywords: non-small cell lung cancer, platinum-based chemotherapy, systemic immune-inflammation index, age-adjusted Charlson comorbidity index, prognostic, overall survival